Bibliometric Analysis on the Use of Artificial Intelligence in Improving the Efficiency of Banking Financial Processes in Southeast Asian Countries - Khuan, Hendri; Judijanto, Loso; Rachmawati, Titiek; Tanjung, Tia; Vandika, Arnes Yuli (West Science Interdisciplinary Studies, 2024)
This bibliometric analysis delves into the utilization of Artificial Intelligence (AI) in enhancing the efficiency of banking financial processes within Southeast Asian countries. With the banking sector in Southeast Asia undergoing rapid technological transformation, AI has emerged as a pivotal force, promising improvements in operational efficiency, risk management, and customer experience. By analyzing the scholarly landscape, including citation metrics, network visualizations, trend analysis, and density visualization, this research uncovers key themes and trends in the adoption of AI in banking across the region. The study not only offers valuable insights into the evolving research domain but also provides guidance for academics, practitioners, and policymakers aiming to shape the future of financial processes in Southeast Asia.